A Systematic Review of Tests for Postcolposcopy and Posttreatment Surveillance. Issue 2 (April 2020) - Clarke, Megan A.; Unger, Elizabeth R.; Zuna, Rosemary; Nelson, Erin; Darragh, Teresa M.; Cremer, Miriam; Stockdale, Colleen K.; Einstein, Mark H.; Wentzensen, Nicolas
Abstract : Objective: For the 2019 ASCCP Risk-Based Management Consensus Guidelines, we conducted a systematic review of diagnostic assays for postcolposcopy and posttreatment management. Materials and Methods: A literature search was conducted to identify articles reporting on tests/assays for cervical cancer screening, triage, postcolposcopy surveillance, and posttreatment surveillance published between 2012 and 2019 in PubMed and Embase. Titles and abstracts were evaluated by co-authors for inclusion. Included articles underwent full-text review, data abstraction, and quality assessment. Pooled absolute pretest and posttest risk estimates were calculated for studies evaluating management of patients after treatment. Results: A total of 2, 862 articles were identified through the search. Of 50 articles on postcolposcopy, 5 were included for data abstraction. Of 66 articles on posttreatment, 23 were included for data abstraction and were summarized in the meta-analysis. The pooled posttreatment risk of cervical intraepithelial neoplasia (CIN) 2+ in all studies was 4.8% (95% CI = 3.4%–6.8%), ranging from 0.4%–19.5% (τ 2 = 0.57) in individual studies. Among individuals testing negative for human papillomavirus (HPV) posttreatment, the risk of CIN 2+ was 0.69% (95% CI = 0.3%–1.5%); among individuals testing positive for HPV posttreatment, the risk of CIN 2+ was 18.3% (95% CI = 12.1%–26.6%) in all studies. All risk estimates were substantially higher for liquid-based cytology. The HPV–cytology co-testing provided slightly better reassurance compared with HPV alone at the cost of much higher positivity. Conclusions: Despite a large number of published studies on postcolposcopy and posttreatment surveillance, only few met criteria for abstraction and were included in the meta-analysis. More high-quality studies are needed to evaluate assays and approaches that can improve management of patients with abnormal screening. Abstract : Supplemental digital content is available in the text.